Out of place : a memoir - Said, Edward W. (New York : Knopf Doubleday Publishing Group, 1999)
"Underscoring all is the confusion of identity as Said had to come to terms with the dissonance of being an American citizen, a Christian and a Palestinian, and, ultimately, an outsider."--BOOK JACKET.
Keywords: Intellectuals -- United States -- Biography